Escalating Medical Negligence in Commonwealth West Africa: Evaluating the Efficacy of Deterrence Mechanism - Ehirim, Ugochukwu Godspower (Universitas Negeri Gorontalo, 2025)
Medical malpractice remains a persistent issue across Commonwealth West-African countries, with limited legal interventions to ensure accountability or deter future occurrences. Despite increasing incidents of medical negligence, both Nigeria and Ghana continue to grapple with the challenge of establishing criminal liability in clear-cut cases. This paper examines the emergent jurisprudential shift signaled by Lagos v Orji, which demonstrates the feasibility of invoking criminal law in medical negligence cases—an area traditionally confined to civil and administrative remedies. Employing a doctrinal methodology and drawing on primary and secondary legal sources, the study explores the shared common law heritage and regional leadership roles of Nigeria and Ghana to assess broader trends in West African legal responses to medical negligence. A key finding of the study is the critical role of social media in raising rights-consciousness and exposing malpractice cases that often escape official documentation. The research highlights a troubling dearth of judicial precedents and underdeveloped jurisprudence on the subject, arguing that the severity and frequency of such cases necessitate a shift toward penal deterrence. The paper underscores the urgency of rethinking legal frameworks to ensure medical accountability, proposing the adoption and refinement of Indonesia’s criminal liability model as a potential roadmap. In advocating for the integration of criminal jurisprudence into the discourse on medical negligence, this study offers a novel contribution to legal scholarship and calls for urgent reform in regulatory and prosecutorial approaches within the region.